Yogyakarta Dalam Perspektif Destinasi Backpacking Travel - Pitaya (Journal of Tourism and Economic, 2021)
Yogyakarta has been famous for domestic and international tourist as designated tourism destination since the tourism industry grew in Indonesia circa 1960’s. Yogyakarta has almost all what the tourist needs and wants. There is no wonder because the tourism destination covers culture, nature, and man made atttractions. Along the historical event of tourism in this area, Yogyakarta become more attractive for many kinds of typical tourist, for the group inclucive tour (GIT), and also for free independent tourist (FIT) or in the current days more popular identified as backpackers. It is very interesting to learn much more about the phenomena, about the dynamic transformation from the cultural tourism destination to the destination for backpacking travel. The tourism components of a destination are certainly very influential in such changing situations. This research aim is to investigate the position and potentials of Yogyakarta from the perspective of backpacking travel. The methods using in this studies is compromising both quantitative and qualitative scheme, whereas quantitative data supported qualitative conclusions using qualitative descriptive analyzis. The quantitative data based on the Yogyakarta Tourism Office data and the qualitative data gathered from the 272 questionaries filled and completed by the backpackers who visiting Yogyakarta and shares about their trip experiences. The result show that for the backpackers, Yogyakarta is “one stop shopping destination”. It is easy to access, easy to explore, consists of many attractions, the nature is challenging, the native people very welcome to the foreigners and above all; for the backpackers as the budget travelers, the traveling cost in this destination is considered cheap and high quality.